2021
DOI: 10.3390/s21217320
|View full text |Cite
|
Sign up to set email alerts
|

Data Collection, Modeling, and Classification for Gunshot and Gunshot-like Audio Events: A Case Study

Abstract: Distinguishing between a dangerous audio event like a gun firing and other non-life-threatening events, such as a plastic bag bursting, can mean the difference between life and death and, therefore, the necessary and unnecessary deployment of public safety personnel. Sounds generated by plastic bag explosions are often confused with real gunshot sounds, by either humans or computer algorithms. As a case study, the research reported in this paper offers insight into sounds of plastic bag explosions and gunshots… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Each fold serves as the validation set once. This process is repeated k times, and the average performance over all folds is calculated to get the final accuracy [5] [14].…”
Section: Proposed Modelmentioning
confidence: 99%
“…Each fold serves as the validation set once. This process is repeated k times, and the average performance over all folds is calculated to get the final accuracy [5] [14].…”
Section: Proposed Modelmentioning
confidence: 99%
“…[ 15 ], to develop a robust predictive model, audio samples must be of high quality. For this purpose, we have collected gunshot-like sounds in different environments [ 16 ]. Additionally, in an effort to maintain a standardization of the data used to generate the model, scaling was carried out in the cepstral domain (see Section 5.2 for details).…”
Section: Data Measurement and Preparationmentioning
confidence: 99%
“…Taking the centroids of each class (see Figure 9 a above) and comparing the relative distances from the gunshot sounds, we arrive at the results shown in Table 4 below. In Table 4 below, it can be observed that the plastic bag pop sound is closest to that of the gunshot sound [ 16 ] (note that “feat2 ” and “feat3” is the x , y coordinate respectively of the centroids of each class (see Figure 9 a above)). Additionally shown in Table 4 below, is a comparative analysis, indicating which sound is closest to the gunshot sound in descending order, namely: plastic bag pop, door knock, door slam, and car backfire.…”
Section: Analysis Toolsmentioning
confidence: 99%
See 2 more Smart Citations